Synthesis and interfacial properties of new 6-sulfate sugar-based anionic surfactants. (22nd June 2021) - Abdellahi, Bemba; Bois, Rémy; Golonu, Sema; Pourceau, Gwladys; Lesur, David; Chagnault, Vincent; Drelich, Audrey; Pezron, Isabelle; Nesterenko, Alla; Wadouachi, Anne
Graphical abstract: Highlights: Sugar-based compounds synthesized as alternative of petroleum-based surfactants. Cyclic and acyclic anionic glycolipids with an amide linkage and sulfate group. Acyclic anionic surfactant with low CMC showed good foaming properties. Abstract: Three families of anionic sugar-based surfactants bearing a sulfate functional group on the primary position of a monosaccharide were synthesized and their physicochemical properties were compared. The first family corresponds to 6-sulfate derivatives of commercially available octa- and dodecyl β-d - gluco - and galactopyranosides. The second and the third families contain an amide linker between the sulfated monosaccharide (galactose, glucose or xylose) and the hydrophobic alkyl chain. Twelve of the as-synthesized anionic glycolipids, including nine novel sulfated compounds, were investigated for their surface activity at the air/liquid interface and for their self-assembling properties. These sugar-based surfactants show surface properties similar to those of commercial anionic surfactants (SDS and SLES) with good ability to reduce surface tension. The obtained results confirm the interest in these new bio-based molecules for potential substitution of anionic surfactants in various formulations.